2019
DOI: 10.15406/japlr.2019.08.00343
|View full text |Cite
|
Sign up to set email alerts
|

Removal of selected metal ions using powder of seeds of Ajwaa dates from aqueous solution

Abstract: At the present time, there is continuous increase of heavy metal burden in our environment, which has become one of the most serious problems globally. Heavy metals cause threat on land and in aquatic life. The problem of metals is significantly attributed by increase of activities from industrial, agricultural, hospital sectors etc. Heavy metals are not degradable, but they are persistent in environments. The aim of this study is to prepare adsorbent from powder of Ajwaa date seeds (PADS). The adsorbent was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Most research has focused on its potential application as an adsorbent for heavy metals in water. These findings in Table 4 are in harmony with those achieved by Mohamed et al and Samra et al [19,27].…”
Section: Chelating Adsorption Of Pb and CD From Milk Samplessupporting
confidence: 90%
See 1 more Smart Citation
“…Most research has focused on its potential application as an adsorbent for heavy metals in water. These findings in Table 4 are in harmony with those achieved by Mohamed et al and Samra et al [19,27].…”
Section: Chelating Adsorption Of Pb and CD From Milk Samplessupporting
confidence: 90%
“…Recent research trends attempt to expand the utilization of agricultural waste adsorbents, like date pits, to extract a wide range of environmental contaminants due to their considerable adsorption capability and low cost [18]. Date pit powder is qualified for eliminating trace levels of toxic metal ions with different functional groups, i.e., hydroxyl, phenolic, carboxylic acid, ester, carboxylate, and amino, which can aid as spots for metal ion adsorption [19]. The efficient use of these low-cost sorbents is primarily attributed to functional oxygenated groups found in lignocellulosic substances, including cellulose and lignin units [20].…”
Section: Introductionmentioning
confidence: 99%
“…Few research studies have used date stones, raw date pits and burnt date pits as potential adsorbents rather dates pit powders for the removal of heavy metals [ 46 , 47 ], while, an enhanced adsorption of heavy metals was reported with the burning of the date seeds. Mohamed et al [ 48 ] reported Cu(II) adsorption using ajwa date pits powder, and the carbonized date seeds for the removal of Cu(II) from wastewater was demonstrated by others [ 49 ]. Our results for Cr(III) and Cd(II) removal using MDP, SDP, TMDP and TSDP were not significantly different from the reported findings in terms of heavy metal adsorption; only the preparation of the adsorbents was slightly different.…”
Section: Resultsmentioning
confidence: 99%
“…According to Hilal et al, 2012 [25], there was rapid adsorption of Cd(II) and Cu(II) in the first 20 minutes, and then the rate of adsorption became slower; this is due to a decreased or lesser number of active sites. Initially, maximum sorption occurs during the adsorption process due to the abundance of vacant adsorbent sites; however, the rate of adsorption eventually decreases, resulting in a straight line plotting the adsorption amount against time, indicating the saturation level of the adsorbent [71]. However, as the contact time increases, the adsorption process may be completed.…”
Section: Contact Timementioning
confidence: 99%